To evaluate the performance of online learning in primary school when pandemi covid-19 in rantau panjang sub district with cipp model - Irzan Irzan; Syarwani Ahmad; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study attempts to describe the evaluation of the implementation of online learning when pendemi covid-19 in elementary school, rantau panjang sub-district, ogan ilir district with cipp model. This study using a qualitative methodology descriptive. case with the approach. The data collection techniques used in this research is a questionnaire, interview and documentation. The data analysis using a method of triangulation and obtain information or data from various sources to verify the data. The research results be concluded that the implementation of online learning when pendemi covid-19 in elementary school, rantau panjang sub-district, ogan ilir district with a model cipp was going pretty good.